The Insistence of Blackness and the Persistence of Antiblackness in Ireland - Mullen, Mary (My University, 2025)
This paper positions Ireland as a critical site for examining the insistence of blackness and an antiblackness created and sustained through Irish ethnonationalist imaginaries and exclusionary processes. Drawing on connected sociologies and Irish Black Studies, this enquiry argues that antiblackness in Ireland operates as a generational force, shaping racial boundaries of belonging for those racialised as Black. Blackness is problematised as both a product of imposed racial frameworks and a generative category, one that resists the confines of traditional diasporic trajectories. This paper advances a rhizomatic understanding of blackness and being Black in the Irish context—as both product and poiêsis—as a form of diasporic linkage. The emergence of Irish Black Studies at Trinity College Dublin offers a critical corrective to dominant frameworks within Irish historiography and sociology, frameworks that erase the epistemic and material presence of blackness in Ireland. By engaging blackness not as a static identity but as a site of rupture and resistance, Irish Black Studies cultivates a disruptive force that redefines the potential for transnational solidarities and epistemic reclamation within and beyond the Irish c
PUBLISHED
Special Issue, 'Epistemic disobedience: Afrocentric theorising of anti-blackness' Open Access
Keywords: Black Irish identity, epistemic erasure, generational antiblackness, Irish Black Studies, situated resistance; Black Irish identity | epistemic erasure | generational antiblackness | Irish Black Studies | situated resistance; Identities in Transformation; Inclusive Society; International Integration; BLACK and MIXED RACE IRISH; Ethnic Politics; European minority cultures and identities; IRELAND; Identity politics and social change; Race and Ethnicity; Race and ethnic studies; Racism/Race Relations; Social attitudes; Sociology; demographic change